Interfacial characteristics and mechanical properties of additive manufacturing martensite stainless steel on the Cu-Cr alloy substrate by directed energy deposition. (10th November 2021) - Zhang, Wenqi; Liao, Hailong; Hu, Zhiheng; Zhang, Shasha; Chen, Baijin; Yang, Huanqing; Wang, Yun; Zhu, Haihong
Highlights: The copper/steel bimetal was successfully fabricated by directed energy deposition. Good metallurgical bonding with crack-free interface was achieved. Crack formation mechanism was discussed in detail. The strength of both the vertically and horizontally combined copper/steel bimetal is investigated. Abstract: Copper/steel is a typical bimetal functional material, combining the excellent electrical and thermal conductivity of copper alloy and the high strength and hardness of stainless steel. There has been recent interest in manufacturing copper/steel bimetal by directed energy deposition (DED) due to its layer-by-layer method. However, cracks tend to form on the copper/steel interface because of the great difference in thermal expansion coefficient and crystal structure between copper and steel. In this work, interfacial characteristics and mechanical properties of the copper/steel bimetal were studied from one layer to multilayers. The laser power has a great influence on the Cu element distribution of the molten pool, affecting the crack formation dramatically on the solidification stage. Cracks tend to form along columnar grain boundaries because of the Cu-rich liquid films and spherical particles in the cracks. Crack-free and good metallurgical bonding copper/steel interface is formed at a scanning velocity of 800 mm/min and the laser power of 3000 W. The ultimate tensile strength (UTS) and the break elongation (EL) of the vertically combined crack-free copper/steel bimetal are 238.2 ± 4.4 MPa and 20.6 ± 0.7%, respectively. The fracture occurs on the copper side instead of the copper/steel interface, indicating that the bonding strength is higher than that of the Cu-Cr alloy. The UTS of the horizontally combined crack-free copper/steel bimetal is 746.7 ± 22.6 MPa, which is 200% higher than that of the Cu-Cr alloy substrate. The microhardness is 398.6 ± 5.4 HV at the steel side and is 235.3 ± 64.1 HV at the interface, which is 400% higher than that of the Cu-Cr alloy substrate. This paper advances the understanding of the interfacial characteristics of heterogeneous materials and provides guidance and reference for the fabrication of multi-material components by DED.